Bone-vascular-adipose tissue interplay: modulation by estrogens - Cepeda, Sabrina Belén (2022)
Nitric oxide (NO) promotes bone cells proliferation, differentiation and survival. An adequate vascularization that provides cell progenitors and hormones is required for skeletal homeostasis. The menopausal hypoestrogenism is tightly associated with bone and cardiovascular diseases, and also with changes in adipose tissue (AT) distribution. In this work we studied the role of the estrogens estradiol (E2) and estrone (E1), and phytoestrogen genistein (Gen) on bone-vascular or bone-AT interactions. Two experimental designs were employed: 1) conditioned medium obtained from endothelial cells (EC) exposed to Gen (CM-EC), or conditioned medium obtained from osteoblasts (OB) exposed to Gen (CM-OB); 2) co-cultures OB-AT. A bidirectional regulation between OB and EC was revealed. CM-EC added to OB monolayers stimulated bone cells proliferation (150% a/C, p<0.05). In the presence of NO synthase (NOS) inhibitor, NAME compound, OB growth was blunted suggesting the participation of NOS system. On the other hand, CMOB added to EC cultured enhanced EC proliferation and migration (44; 150% a/C respectively, p<0.01). Since these two events are involved in angiogenesis, tubes formation from aortic rings seeded on a collagen matrix was quantified. CM-OB induced a 0.5 fold increase (p<0.05) in tubes formation around the rings. To assess bone-AT interactions, cocultures OB-AT were used. After 3 days, E2 E1 and Gen stimulated NO production (64; 34; 37% s/c, respectively). At a longer co-culture time, a reduction in NOS activity accompanied by an increase in oxidative stress, measured as hydrogen peroxide production, was detected (1090 ± 37.1 vs 1220 ± 31.2 nmol H2O2/ mg prot, C vs E2, p<0.01). When AT slices were removed, OB diminished their capability to enhance NO synthesis and, to mineralize extracellular matrix (Alizarin staining) in response to estrogens. In summary, estrogens favour bone vascular interactions, but in the presence of AT osteoblastogenic response is delayed.